EVALUASI KLAIM KONSTRUKSI DALAM PERSEPEKTIF KONTRAKTOR UTAMA DAN SUBKONTRAKTOR - Abadi, Ilham; Utomo, Jati; Sukamta, Sukamta (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
Complexity in construction projects tend contractors to share the works to subcontractors. The subcontractor's role has a high influence on project completion. However, in project, disputes between subcontractor and main contractor arise regarding compliance of rights and obligations that impact to claims. This research was conducted to evaluate construction claims from the perspective of subcontractors and contractors related with types of claims, the drive and resistance”™s factors for claims, the impact of claims, total amount of claims, and characteristics of subcontractors. The research method was carried out by distributing questionnaires, interviews, and case studies of projects based on perspective of the contractor and subcontractor. The results of the analysis show that claims for variation order, extension of time and price adjustments are the types of claims regularly occurred; driving”™s factor of claims due to price increases, late of payments and acceleration of the works; the resistance”™s factors for claims are due to lack of understanding of the contract, poor communication, incomplete documents; and the impact of claims are the increase in the cost budget, time of construction, and relationships; regarding total amount of claim with range 1-20 billion; then for subcontractor”™s characteristic, mostly foreign subcontractor regularly propose to claim.